Application of the Internet of Thing in Green Agricultural Products Supply Chain Management - Lin Li (2011 International Conference on Intelligent Computation Technology and Automation, 2011)
Green supply chain management of agricultural products, whose establishment of trace ability is important, but the lack of appropriate information technology supported in the past. Green agricultural supply chain trace ability system should be established to provide a guarantee with the development of the internet of things. Analysis based on the internet of things in the green agricultural supply chain applications, we can draw the following conclusions: Firstly, the internet of things has been gradually manifest advantage in the green supply chain management of agricultural products, and represents the future direction of agricultural information. Secondly, the current of the internet of things between applied research and practical applications there is a gap in the agricultural supply chain. The Internet of Things in China some of the key technology is still in training stage in the green agricultural application of supply chain management. Thirdly, physical aspects of the use of the Internet of Thing is different between different green products.